The relationship between life events and daily hassles, self-efficacy expectations, coping strategies and psychosomatic health - Χ. Καραδήμας, Ευάγγελος; Καλαντζή-Αζίζι, Αναστασία (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF